Pengaruh Sistem Manajemen Layanan Berbasis IoT, Cloud ERP, dan Green Operation Management terhadap Kinerja Operasional Berkelanjutan di Terminal Teluk Lamong dengan Efisiensi Operasional Sebagai Variabel Mediasi - Erwan Khanissuma; Siti Mujanah; Achmad Yanu Alif Fianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In facing the increasingly complex challenges of the port industry, it is important to understand the contribution of technology and green practices in improving efficiency and sustainable operational performance. This study aims to examine the effect of IoT-based Service Management System (X1), Cloud ERP (X2), and Green Operation Management (X3) on Sustainable Operational Performance (Y), with Operational Efficiency (Z) as a mediating variable at Lamong Bay Terminal. Data were collected through questionnaires distributed to workers who have implemented IoT, Cloud ERP, and green operations management practices. Data analysis used the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to evaluate the relationship between variables. The results showed that IoT, Cloud ERP, and Green Operation Management have a positive influence on operational efficiency with coefficient values of 0.299; 0.166; and 0.099, respectively. Operational efficiency also contributes positively to the sustainability of operational performance with a coefficient value of 0.263. These findings suggest that the implementation of modern technology and environmentally friendly practices can support improved operational efficiency and sustainability. These results provide strategic insights for Teluk Lamong Terminal to optimize operational efficiency and sustainable performance